Changes in Emotions Over the Course of Dialectical Behavior Therapy and the Moderating Role of Depression, Anxiety, and Posttraumatic Stress Disorder. Issue 6 (November 2020) - Fitzpatrick, Skye; Bailey, Katharine; Rizvi, Shireen L.
Abstract: Evidence-based borderline personality disorder (BPD) treatments such as dialectical behavior therapy (DBT) emphasize the acquisition and use of strategies to down regulate negative emotion. However, little research examines whether specific emotions change during DBT. Further, it is unclear if BPD-relevant comorbidities that involve heightened emotion—namely, depression, anxiety disorders, and posttraumatic stress disorder (PTSD)—moderate these outcomes. This study investigated which specific emotions (hostility/anger, fear, shame/guilt, and sadness) decrease during DBT, and whether comorbid depression, anxiety disorders, and PTSD moderate these outcomes. Individuals with BPD ( N = 101) completed 6 months of standard DBT and provided measurements of specific emotions at every session and at pre-, mid-, and posttreatment. Generalized estimating equations revealed moderate effect-sized reductions in anger at major assessment time points. Anxiety disorders and PTSD moderated the effect of time on fear, shame, and guilt. PTSD also moderated the effect of time on sadness. For all moderating effects, individuals with the comorbidity exhibited greater reductions than those without. These findings corroborate that DBT reduces several specific emotions, and comorbid PTSD and anxiety disorders may facilitate this effect for fear, shame/guilt, and sadness (clinical trial registration number = NCT03123198). Highlights: Examined which specific emotions change in dialectical behavior therapy (DBT) DBT completed by 101 individuals with borderline personality disorder There were moderate effect-sized reductions in anger Those with PTSD had greater reductions in shame/guilt, sadness, and fear Those with anxiety disorders had greater reductions in shame/guilt and fear